Design of pH Measuring Equipment for Liquid Waste from Coal Mining Using Arduino Uno - Safrianti, Ery; Feranita; Nurhalim; Wahyu Dwi Reza (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2022)
In coal mining, to check the pH content of the water in the liquid waste from coal mining, most of the mining workers use conventional methods, namely by measuring using a digital pH meter or litmus paper periodically. Manual pH reading system makes handling slow. Based on these reasons the researchers designed a tool that can monitor pH values, the working principle of this tool is that the pH electrode is inserted into the sample solution, then the electrode detects the sample solution and changes the electrical signal, where the output will be amplified by an amplifier circuit in the form of an analog voltage, then on Arduino uno analog data is converted to digital data or ADC (Analog To Digital Conversion) after which it is converted again to pH value and displayed on an LCD that has been equipped with I2C. And this tool is also equipped with an RTC (Real Time Clock) so that it can display the time at which pH data is taken in the waste. The results of the calibration of the pH sensor obtained a linear equation, namely, Y = 25.84 - 7.1211X so that the designed tool has an error percentage of the manufacturer's pH meter tool of 1.028 %. By using this tool, the writer concludes that 0.4 grams of camphor (CaO) on the prototype or 480 kg in real conditions with a pool area of 600 m^3 can reduce the output voltage on the pH sensor from 3.20 V to 2.56 V thereby increasing the pH value. from 3.07 to 7.58 in pool 4 or drain pool.